MARA - Mobile Augmented Reality for Advertising - Ferreira, Andreia Marina Serrano (2015)
The use of applications for mobile devices applied to advertising has been increasing during the last few years, being more interactive, not requiring a large monetary investment and reaching a large number of users. The aim of this dissertation is to create an application in mobile Augmented Reality for advertising/divulgation (MARA), and it was decided that an application for turism divulgation in Covilhã would be developed. The developed application aims to present a tourist route in Covilhã, which gives information through Augmented Reality, in the various waypoints. This application also makes use of geolocation systems (GPS) that guides users through the various points. Augmented Reality (AR) is like a supplement to the real world using virtual objects created with computer graphics. This technology is expanding, its applications are varied and their diversity has been increasing, being used in several areas. In this dissertation there are examples of applications in areas such as advertising and marketing, medical, entertainment, military, education and finally tourism. The application described in this paper was developed for Android using the Apache Cordova, Wikitude and Google Maps. Android is an operating system (OS) for mobile devices based on Linux. It is the OS for mobile devices with more users in the world. Being open source it facilitates the work of developers in the application development process as well as its publication in the Play Store (Android application store). Being this application a browser application, Apache Cordova was needed to its execution. This framework facilitates the creation of applications for mobile devices, since these will be developed using HTML, CSS and JavaScript, without having to code in Java. To create the functionalities of the application it was necessary Wikitude, a plugin to perform the AR, as well as Phonegap Google Maps plugin for maps and directions, presented in the application.